Pengaruh substitusi tepung terigu dengan tepung porang (amorphophallus oncopphyllus) terhadap kadar protein, serat pangan, lemak, dan tingkat penerimaan biskuit - Mahirdini, Silmi; Afifah, Diana Nur (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background : It is associated with a healthy lifestyle in the prevention of cardiovascular disease risk with consumption of low-fat foods and increased consumption of dietary fiber, which can be obtained from porang flour. One of processed food products consumed by many people is a biscuit. This study aims to determine the effect of different substitution of wheat flour with porang flour on protein content, dietary fiber content, fat content, and acceptance level of biscuits.Methods : Experimental research with a completely randomized design with 4 variations of flour and porang flour substitution each 0: 100%, 30: 70%, 60: 40%, and 100: 0%. Statistical analysis of protein levels using the Kruskal-Wallis test, while statistical analysis of levels of dietary fiber, and fat using One Way ANOVA 95% with Tukey test for further analysis. The results of organoleptic test used Friedman test and Wilcoxon test for further analysis.Results : Highest protein content contained in a biscuit with substitution of 100% flour porang and 0% flour, levels of dietary fiber soluble and insoluble highest in substitution of 40% of porang flour and 60% wheat flour and fat content was lowest for the biscuits with the substitution of 100% 0% porang flour and wheat flour. Based on the results of acceptance level, the closest biscuits are biscuits with a control group of 40% substitution porang flour and 60% wheat flour.Conclusion : Substitution porang flour and wheat flour in making of biscuits to give effect to the levels of soluble dietary fiber and insoluble, fat content, and the level of acceptance.